Tadabbur - storytelling as an approach for mental health support at the Centre for Foundation Studies, IIUM - Mohd. Basri, Mohd. Rafaei; Ahmad Azam, Nur Nabila; Abu Hasan, Nurliyana; Jaafar Sidek, Mohd Farid; Abu Hassan, Siti Farhana; Aling, Noor Asiah (2022)
The National Health and Morbidity Survey (NHMS) conducted by the Ministry of Health (MoH) in 2015 revealed that the prevalence of mental health problems among those 16 years and above was 29.2%. 1 in 3 Malaysians have mental health issues, with highest prevalence among those aged 16-19 years as well as those from low-income families. Hence, the study suggests an integrated and supplementary approach in dealing with mental health issues at the Centre for Foundation Studies, IIUM. The proposed approach integrates the practice of tadabbur (in-depth reflection) on selected exemplary figures and stories from the Al-Quran with the conventional methods in dealing with the mental health issues. The selected figures and stories are analysed in the context of mental health intervention and supports. As an alternative approach, the methods of implementation of the approach rely on the tadabbur of Quranic verses and effective storytelling. The novelty of using the tadabbur-storytelling method in tackling the mental health issues is the core foundation of this approach. The responses collected from the participants i.e., students and staff, have been very encouraging towards the new approach and can be seen from the results of the survey conducted.